PERUBAHAN SOSIAL EKONOMI MASYARAKAT TRANSMIGRAN JAWA DI DESA TALANG PAMESUN KECAMATAN JUJUHAN KABUPATEN BUNGO PROPINSI JAMBI (1993-2007) - Sunarti, Emi; Husnita, Liza; Sabar, Sabar (Pendidikan Sejarah, 2013)
ABSTRACT This article discusses the Socio-Economic Change in Rural Java Community Transmigrants Pamesun Talang District Jujuhan Bungo Jambi Province from 1993 to 2007 . The formulation of the problem in this study are as follows : How can the development community in the village Talang Javanese transmigrants Pamesun , then about the socio-economic life of the people in the village Talang Javanese transmigrants Pamesun and how forms of social and economic change in the Javanese transmigrants Pamesun the village Talang . This article aims to look at how the social changes in the Java Community Economic Migrants village Talang District Pamesun Jujuhan Bungo Jambi .The Ricseance method used is the method of historical stages : ( 1 ) heuristic of finding and collecting information from primary and secondary sources . ( 2 ) Criticism Sources include internal and external criticism , namely by testing for authenticity and kesahian information . ( 3) Interpretation of interpreting and connecting the existing facts . ( 4 ) Historiography of the presentation of the results of a research thesis .The results showed that the socio - economic conditions of the people in the village Talang Javanese transmigrants Pamesun have ups and downs which have not seen the beginning of 1993 social and economic change , but in the year 2002 -an increase socio - economic field when viewed from : income , education , and social activities . Then towards the late 2007 decline in the level of social welfare , which is caused by the economic downturn . Reduced levels of livelihood , automated influential towards the welfare of Migrants . Keywords: regional ,growth, power, rule